2016
DOI: 10.1212/cpj.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

Language barriers between physicians and patients are not associated with thrombolysis of stroke mimics

Abstract: Background: Acute stroke is a time-sensitive condition in which rapid diagnosis must be made in order for thrombolytic treatment to be administered. A certain proportion of patients who receive thrombolysis will be found on further evaluation to have a diagnosis other than stroke, so-called "stroke mimics." Little is known about the role of language discordance in the emergency department diagnosis of acute ischemic stroke. Methods: This is a retrospective analysis of all acute ischemic stroke patients who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The diversity of healthcare providers and interpreter/tele-interpreter service may have overcome language barriers. Our IVT rate and DTN time are comparable or better than what were reported recently from other Comprehensive Stroke Centers [ 14 , 19 , 21 , 22 , 24 ]. We have also shown that increased age and higher initial NIHSS scores were associated with unfavorable outcomes at hospital discharge.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The diversity of healthcare providers and interpreter/tele-interpreter service may have overcome language barriers. Our IVT rate and DTN time are comparable or better than what were reported recently from other Comprehensive Stroke Centers [ 14 , 19 , 21 , 22 , 24 ]. We have also shown that increased age and higher initial NIHSS scores were associated with unfavorable outcomes at hospital discharge.…”
Section: Discussionsupporting
confidence: 87%
“…Emergency medical service usage was actually reported higher in the Spanish-speaking patients than the English-speaking patients treated with IVT [18]. A retrospective single-center study showed that language discordance was not associated with acute stroke misdiagnosis among patients treated with IVT [19]. Another study reported reduced mortality in patients with language barriers [13].…”
Section: Discussionmentioning
confidence: 99%
“…A second study investigated the role of language-concordant vs. discordant encounters, defined by whether the primary treating physician and the patient possessed fluency in the same language. The proportion of stroke mimics was not shown to differ between the two groups, nor did it differ between patients who selfreported as primarily English or Spanish speakers (19). The third related study observed no differences in median doorto-imaging (DTI) time, imaging-to-needle (ITN) time, or DTN time between language-concordant and discordant groups (20).…”
Section: Pre-stroke Care: Awareness and Preventive Treatmentmentioning
confidence: 87%
“…Two studies found no association between English or non-English preference and either mode of arrival or time to hospital presentation (17,32). Three studies were carried out at the same New York City institution using data from patients who received IV-tPA (18)(19)(20). One found that Spanish speakers were more likely than English speakers to have arrived by EMS after adjusting for confounders, while prenotification rates were not significantly different among those who utilized EMS.…”
Section: Pre-stroke Care: Awareness and Preventive Treatmentmentioning
confidence: 99%
“…However, at our center, we have previously shown that tPA treatment among eligible patients did not differ between English and Spanish speakers. 17 Additionally, the generalizability of our findings to other geographic areas may be limited.…”
Section: Discussionmentioning
confidence: 89%